English Lexical Bundles in The Graduate Theses: The Frequency, Structure and Distribution - Mohamad Syihabuddin Faqih; Ignatius Harjanto (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2022)
Lexical bundles are one of the important characteristics of academic discourse which tell readers to know whether the writer is professional or novice. Inevitably, studies on lexical bundles in scientific essays are important to do. This study identifies the most frequent, structural characteristics, and the functional categorization of lexical bundles in the Master Theses in Teaching English as a Foreign Language (TEFL), specifically in the Findings and Discussion section. There were 651.083 words from 74 different theses compiled to create the corpus by using Antconc 3.5.8. The results found 117 different lexical bundles and the sequences ‘the result of the’ and ‘on the other hand’ dominate the section. Noun phrase + of structure which covers one third of overall forms in the corpus were the most lexical bundles’ structural types in the findings and discussion section followed by other noun phrase structures (22% out of overall bundles). Functionally, research-oriented bundles (45% of overall bundles) were the most frequent ones followed by text-oriented (40%) and the least frequent bundles were participant-oriented. Reported findings are further discussed with related theories.